Van Gogh and the avant-garde along the Seine - Hellman, Charlotte; Hoeven, Joost van der; Lespinasse, François; Meedendorp, Teio; Thomson, Richard 1953- (The Art Institute of Chicago, 2023)
"From 1881 to 1890, Vincent van Gogh, Georges Seurat, Paul Signac, Emile Bernard, and Charles Angrand chose Asnières, a suburb of Paris, as a site of artistic experimentation. Located on the Seine, Asnières became a popular destination for Parisians thanks to aquatic sports and festivals starting in the 1850s, facilitated by the arrival of new train stations and bridges earlier in the century. This convenient new transportation system had beckoned Parisians to more distant destinations like Argenteuil and Bougival, resulting in the river scenes depicted by Impressionists like Monet and Renoir. At the same time, the idyllic landscape of Asnières increasingly contrasted with the factories appearing on the opposite side of the river. Homing in on the tensions between leisure and work, the avant-garde artists at Asnières sought to capture the feeling of this starkly modern landscape by developing innovative motifs, styles, and techniques that pushed their work in new directions. Offering an unprecedented in-depth look at the work produced by the artists at Asnières, this illustrated volume includes scholarly essays on each of the artists as well as a map detailing the locations where the artists painted."--
Impressum: This catalogue was published in conjunction with the exhibition "Van Gogh and the Avant-Garde: The Modern Landscape", ... exhibition dates: "Van Gogh and the Avant-Garde: The Modern Landscape", The Art Institute of Chicago, May 14 - September 4, 2023; "Van Gogh Along the Seine", Van Gogh Museum, Amsterdam, October 13, 2023 - January 14, 2024
Zusatz auf Cover: Van Gogh, Seurat, Signac, Bernard, Angrand
Keywords: Gogh, Vincent van -- 1853-1890; Bernard, Emile -- 1868-1941; Signac, Paul -- 1863-1935; Angrand, Charles -- 1854-1926; Seurat, Georges -- 1859-1891; Avantgarde; Gogh, Vincent van / 1853-1890 / Exhibitions; Gogh, Vincent van / 1853-1890 / Travel / France / Asnières-sur-Seine; Gogh, Vincent van / 1853-1890 / Friends and associates; Seurat, Georges / 1859-1891 / Exhibitions; Signac, Paul / 1863-1935 / Exhibitions; Bernard, Emile / 1868-1941 / Exhibitions; Angrand, Charles / 1854-1926 / Exhibitions; Avant-garde (Aesthetics); Seine River (France) / In art / Exhibitions; Landscapes in art / Exhibitions; Influence (Literary, artistic, etc.); Gogh, Vincent van / 1853-1890; Friendship; Travel; France / Asnières-sur-Seine; exhibition catalogs; Exhibition catalogs; Ausstellungskatalog -- Art Institute of Chicago -- 14.05.2023-04.09.2023 -- Chicago, Ill.; Ausstellungskatalog -- Van Gogh Museum -- 13.10.2023-14.01.2024 -- Amsterdam